Melanin-concentrating hormone (MCH) modulates C difficile toxin A-mediated enteritis in mice. Issue 1 (29th September 2008) - Kokkotou, E; Espinoza, D O; Torres, D; Karagiannides, I; Kosteletos, S; Savidge, T; O'Brien, M; Pothoulakis, C
Abstract : Objective: Melanin-concentrating hormone (MCH) is a hypothalamic orexigenic neuropeptide that regulates energy balance. However, the distribution of MCH and its receptor MCHR1 in tissues other than brain suggested additional, as yet unappreciated, roles for this neuropeptide. Based on previous paradigms and the presence of MCH in the intestine as well as in immune cells, its potential role in gut innate immune responses was examined. Methods: In human intestinal xenografts grown in mice, changes in the expression of MCH and its receptors following treatment with Clostridium difficile toxin A, the causative agent of antibiotic-associated diarrhoea in hospitalised patients, were examined. In colonocytes, the effect of C difficile toxin A treatment on MCHR1 expression, and of MCH on interleukin 8 (IL8) expression was examined. MCH-deficient mice and immunoneutralisation approaches were used to examine the role of MCH in the pathogenesis of C difficile toxin A-mediated acute enteritis. Results: Upregulation of MCH and MCHR1 expression was found in the human intestinal xenograft model, and of MCHR1 in colonocytes following exposure to toxin A. Treatment of colonocytes with MCH resulted in IL8 transcriptional upregulation, implying a link between MCH and inflammatory pathways. In further support of this view, MCH-deficient mice developed attenuated toxin A-mediated intestinal inflammation and secretion, as did wild-type mice treated with an antibody against MCH or MCHR1. Conclusion: These findings signify MCH as a mediator of C difficile -associated enteritis and possibly of additional gut pathogens. MCH may mediate its proinflammatory effects at least in part by acting on epithelial cells in the intestine.